PENINGKATAN KETERAMPILAN MEMBACA MELALUI STRATEGI KNOW WANT TO LEARN (KWL) - Karmilasari Karmilasari (Institut Agama Islam Negeri Palopo, 2018)
The aim of this research is to apply Know Want to Learn strategy to improve reading skill in second grade students of SDN 245 Temboe. This research is a type of Classroom Action Research (PTK) conducted in collaboration with teachers through the use of Hopkins model consisting of 4 stages of planning, implementation, observation, and reflection. The subjects of the study were the students of class II SDN 245 Temboe which amounted to 19 students. The data collection technique used is by observation, test and documentation. The research data obtained is analyzed by using statistical formula (percentage) to express descriptively the research result. Furthermore, to discuss and explain the results of research that is quantitative descriptive then used data analysis techniques by reduction, presentation and drawing conclusions. With the implementation of Know Want to Learn (KWL) strategy can improve reading skill in second grade students of SDN 245 Temboe, the improvement is proved by the increasing of average score of students reaching Minimum Exhaustiveness Criteria (KKM) and number of students on pre-action test reaching KKM amounted to 26.31% with an average score of 59, in the first cycle the number of students who reached the KKM of 47.36% with an average score of 66, and in the second cycle the number of students who reached the KKM of 94.73% 85. Thus, the reading skill in class II SDN 245 Temboe by applying the Know Want to Learn strategy (KWL) conducted from the first cycle to the second cycle shows significant results.